PAX6-dependent differentiation landscape of ocular surface epithelium via single-cell RNA sequencing in hiPSC-derived ocular developmental organoid - Rei Kamuro; Masahito Yoshihara; Susumu Hara; Takahiro Nemoto; Laura Howard; Ai Honda; Ayano Yamamoto; Toru Takigawa; Susumu Sakimoto; Koichi Baba; Andrew J. Quantock; Kohji Nishida (Communications Biology)
Abstract During eye development, surface ectoderm cells that express PAX6 differentiate into corneal, limbal and conjunctival epithelia. However, several aspects of this differentiation process -- such as the developmental origin of the limbal epithelium and the mechanisms that underlie PAX6-mediated lineage specification -- are not properly understood. To explore these issues, we used single-cell RNA sequencing to study ocular surface epithelial cells derived from human induced pluripotent stem cells. Our analysis reveals that the corneal and conjunctival epithelial cell lineages originate from the surface ectoderm, and that the conjunctival lineage contributes to limbal epithelial cell populations. We also show that primordial conjunctival epithelial cells express limbal epithelial markers before lineage bifurcation. Finally, the activity and expression of PAX6 are highest in corneal epithelial cells, followed by those of the limbal epithelium and conjunctival epithelium, suggesting that lineage-specific differentiation is regulated by levels of PAX6 activity. These findings provide deeper understanding of the early-stage human ocular surface development.